2010
DOI: 10.1080/10934521003648784
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of nitrogen-containing pollutants by novel ferrate(VI) technology: A review

Abstract: Nitrogen-containing pollutants have been found in surface waters and industrial wastewaters due to their presence in pesticides, dyes, proteins, and humic substances. Treatment of these compounds by conventional oxidants produces disinfection by-products (DBP). Ferrate(VI) (Fe(VI)O(4)(2-), Fe(VI)) is a strong oxidizing agent and produces a non-toxic by-product Fe(III), which acts as a coagulant. Ferrate(VI) is also an efficient disinfectant and can inactivate chlorine resistant microorganisms. A novel ferrate(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(58 citation statements)
references
References 185 publications
(164 reference statements)
2
56
0
Order By: Relevance
“…But no obvious intermediates were found in the present study. The present study and previous studies (Lee and von Gunten, 2010;Noorhasan et al, 2010;Sharma, 2010) showed that Fe(VI) can react with dissolved organic nitrogen compounds. Oxidation of nitrogen-containing compounds by Fe(VI) can proceed through either one-electron or two-electrons processes to yield non-hazardous oxidation products (Sharma, 2010).…”
Section: 3mentioning
confidence: 90%
See 2 more Smart Citations
“…But no obvious intermediates were found in the present study. The present study and previous studies (Lee and von Gunten, 2010;Noorhasan et al, 2010;Sharma, 2010) showed that Fe(VI) can react with dissolved organic nitrogen compounds. Oxidation of nitrogen-containing compounds by Fe(VI) can proceed through either one-electron or two-electrons processes to yield non-hazardous oxidation products (Sharma, 2010).…”
Section: 3mentioning
confidence: 90%
“…The present study and previous studies (Lee and von Gunten, 2010;Noorhasan et al, 2010;Sharma, 2010) showed that Fe(VI) can react with dissolved organic nitrogen compounds. Oxidation of nitrogen-containing compounds by Fe(VI) can proceed through either one-electron or two-electrons processes to yield non-hazardous oxidation products (Sharma, 2010). The k values decrease in the order of aniline > glycine (primary amine) > dimethylamine (secondary amine) > trimethylamine (tertiary amine) in the pH range 6e8 (Lee and von Gunten, 2010;Noorhasan et al, 2010).…”
Section: 3mentioning
confidence: 90%
See 1 more Smart Citation
“…The removal efficiency mainly depends on the reactivity of Fe(VI) to target micropollutants and coexisting constituents present in source water (Lee and von Gunten, 2010). Fe(VI) has been known to react with electron-rich organic moieties, such as phenols, anilines, amines, and olefins through electrophilic oxidation mechanism (Hu et al, 2009;Lee et al, 2009;Yang et al, 2012;Sharma, 2010Sharma, , 2013. The corresponding second-order reaction rate constants range from >1 to 10 5 M À1 s À1 in aqueous solution (Lee et al, 2009;Sharma, 2013).…”
mentioning
confidence: 99%
“…All important topics are covered, e.g., general information on common types of sulfonamides polluting the environment (Baran et al 2011;Zhang and Li 2011), sample preparation (Namera et al 2011;Samanidou and Karageorgou 2011), and analytical methods used for sulfonamide detection, namely HPLC (Seifrtova et al 2009;Tolika et al 2010), capillary electrophoresis (Garcia-Campana et al 2009;Pinero et al 2011), and immunoassays (Nesterenko et al 2009). Some reviews deal with resistance (Le-Minh et al 2010;Jury et al 2011), or the degradation of different pollutants, sulfonamides included (Sharma 2010). The same topics Contamination of the environment, mainly soil and surface water, is a worldwide problem.…”
Section: Basic Analysis Of Publications On Sulfonamides In the Enviromentioning
confidence: 99%